Differentiated roles of mean climate and climate stability on post-glacial birch distributions in northern China. (November 2019) - Qian, Hao; Hongyan, Liu; Shilei, Yang; Weihua, Yang; Zhaoliang, Song
Past changes in the distribution of tree species are critical to predict future vegetation dynamics under changing climate conditions. In this study, pollen-based reconstruction with 60 pollen records from mid-latitude region was performed in China. Betula emerged after the Last Glacial Maximum (LGM), when the climate ameliorated gradually. The distribution range was small but increased significantly during the early Holocene. However, when the climate was wet and warm during the mid-Holocene, the distribution range did not continue to expand. The relationships between the percentages of Betula pollen and the strength of the East Asian summer monsoon (EASM) or its variability were positively correlated, while those of Betula and Pinus had opposite trends in the study region. Besides, the post-glacial distribution dynamics of Betula platyphylla and Betula dahurica were influenced by climate change which were simulated by species distribution models (SDMs). We conclude that birch distribution in mid-latitudinal northern China was mainly driven by the EASM or its variability, especially during the LGM and early Holocene when the climate was unstable, while the replacement by Pinus and Quercus occurred during the mid-Holocene when the climate remained stable. The future unstable climate may benefit birch development.